Cognitive impairment and its association with cholinergic dysfunction in Parkinson's disease. Issue 6 (19th June 2020) - Baba, Toru; Takeda, Atsushi
Abstract: Cognitive impairment is an important nonmotor symptom in Parkinson's disease (PD). In recent years, much research has focused on cholinergic dysfunction as a principal cause of early cognitive decline in PD. Cholinergic dysfunction is common and produces characteristic impairments in multiple cognitive domains; furthermore, it is associated with future dementia in PD. Recently, it has become possible to measure the volume of the human cholinergic nucleus, and this technique has been increasingly applied in PD research. Here, we review the current state of knowledge on cognitive dysfunction and neuroimaging studies, with particular focus on atrophy of the cholinergic nucleus in PD.